Neuraxial anesthesia versus general anesthesia in patients undergoing three-dimensional laparoscopic radical prostatectomy: Preliminary results of a prospective comparative study - Stefano Alba; Deborah Fimognari; Fabio Crocerossa; Luigi Ascalone; Carmine Pullano; Fernando Chiaravalloti; Francesco Chiaradia; Umberto Carbonara; Matteo Ferro; Ottavio de Cobelli; Vincenzo Pagliarulo; Giuseppe Lucarelli; et al. (Asian Journal of Urology, 2023)
Objective: Neuraxial anesthesia (NA) showed to reduce both morbidity and mortality in patients undergoing laparoscopic surgery. We aimed to investigate the use of NA in patients undergoing transperitoneal three-dimensional laparoscopic radical prostatectomy (t-3DLRP) and compare the intraoperative and postoperative outcomes with a control group of patients undergoing t-3DLRP under general anesthesia (GA). Methods: A prospective, double-center, double-surgeon study cohort of 84 consecutive patients undergoing t-3DLRP between June 2019 and June 2021 was analyzed. A study group of 42 patients undergoing t-3DLRP under NA was compared with a control group of 42 patients undergoing t-3DLRP under GA. Results: The two group were similar in all demographic, clinical, and pathological variables. Postoperative blood gas parameters were within physiologic limits in both groups. Muscle relaxation was adequate for surgery during both NA and GA. Median length of stay was 1 day shorter for NA group than GA group (5 days vs. 6 days, p=0.05). t-3DLRP under NA had a statistically lower rate of minor complications (4.8% vs. 19.0%, p=0.03) and less postoperative pain (median numeric rating scale 3 vs. 4, p=0.01) compared to GA. No major complications were observed in both groups. Significantly more patients were willing to undergo a similar intervention under NA than GA (p=0.04). Conclusion: t-3DLRP under NA is a feasible and safe procedure, with less postoperative pain and fewer minor complications than the same procedure under GA. NA allows the maintenance of muscle relaxation and respiratory excursions without interfering with surgery.